Comparison of anterior segment optical coherence tomography versus technician led gonioscopy as a triage tool for anterior chamber angle status - Dhalla, Amit; Evans, Thomas; Pilling, Joshua; Auger, Graham (Eye (London), 2025)
Objective Can anterior segment optical coherence tomography (AS-OCT) replace gonioscopy as the preferred triage tool for angle assessments in virtual glaucoma clinics? Subjects/Methods Every new referral into Sheffield Teaching Hospital’s glaucoma service over a five-month period were subject to gonioscopy and AS-OCT assessment of their angles. Appropriately trained ophthalmic science practitioners (OSPs) performed the gonioscopy and labelled angles as ‘open’ or ‘closed’. Two glaucoma-subspecialty ophthalmologists reviewed the AS-OCT images independently on a different day and graded the angles as ‘open’ or ‘closed’. Results There was an angle assessment of 384 eyes, with statistical analysis of 358 eyes due to 26 eyes being unable to have gonioscopy. AS-OCT was found to have a sensitivity of 97.11% ± 1.32% and a specificity of 36.17% ± 9.71% for identifying an open angle. The positive predictive value of the test was 95.70% ± 0.63%, while the negative predictive value was 46.08% ± 13.13%. Conclusions As a triage tool, specialist assessment of the angle on AS-OCT is a safe, effective alternative to OSP-led gonioscopy.